Axiological Harmonization of Sharia Economic Law Supremacy and DSN-MUI Fatwa in Indonesia - Moh. Asep Zakariya Ansori; Royani; Mugni Muhit; Irvan Hilmi; Mohamad Anton Athoillah (Al Mashalih - Journal of Islamic Law, 2023)
This study aims to upgrade the position of the Compilation of Sharia Economic Law (KHES) and Fatwa DSN-MUI to become a law. This is because it is very urgent to immediately publish the draft to be ratified. Because KHES and DSN-MUI Fatwa are special rules that regulate the operational system and dispute resolution of Islamic economics, apparently its position is very strategic in the scope of Islamic economics. In addition to the urgency of the position of KHES and Fatwa of the National Sharia Council, it also contains weaknesses in the existence of National law. This is because its existence is not a source of law that has the legality of national law. As Law No. 12 of 2011 concerning the Formation of Legislation, does not mention fatwa as part of the legal basis in this country, Fatwa is just an opinion or advice conveyed by Islamic law experts who are members of an organization. The Fatwa of the National Sharia Council contributed to the birth of the Compilation of Sharia Economic Law. This is certainly a breakthrough related to the legality of sharia economic law. However, the existence of KHES is a reference for Religious Court Judges as a settlement of disputes, but KHES is not in the form of a law, in fact it is only a PERMA, and this certainly affects the legal force of national legislation. Therefore, to harmonize and formulate the National Sharia Council Fatwa into KHES and raise the status of KHES to become a law is important.